1996
DOI: 10.1021/ma951026r
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Crystal Formation Coupled with the Coil−Helix Transition in the Ternary System Poly(γ-benzyll-glutamate)/Dichloroacetic Acid/Dichloroethane

Abstract: Phase behavior and ordering characteristics were reported for poly(γ-benzyl l-glutamate) (PBLG) in a mixed solvent containing a denaturant acid, dichloroacetic acid (DCA), + dichloroethane (DCE). The solutions of PBLG prepared so as to be liquid crystal at room temperature were observed to undergo a reentrant isotropic transition at low temperature where conformational disordering of PBLG molecules takes place. The deuterium quadrupolar splitting data obtained by the 2H NMR method were analyzed to elucidate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 23 publications
0
51
0
Order By: Relevance
“…Poly(g-benzyl-L-glutamate)-b-poly(propylene oxide)-b-poly(g-benzyl-L-glutamate) (PBLG-b-PPO-b-PBLG) triblock copolymers were synthesized by ring-opening polymerization of g-benzyl-L-glutamate-N-carboxyanhydride (BLG-NCA) initiated by NH 2 -PPO-NH 2 [46][47][48]. NH 2 -PPO-NH 2 (0.2 g; 0.05 mmol) and BLG-NCA (2.7 g; 10 mmol) was dissolved in dioxane separately in two flame-dried reaction bottles, then, BLG-NCA solution was added to the solution of NH 2 -PPO-NH 2 via a transfer cannula.…”
Section: Polymer Synthesis and Characterizationmentioning
confidence: 99%
“…Poly(g-benzyl-L-glutamate)-b-poly(propylene oxide)-b-poly(g-benzyl-L-glutamate) (PBLG-b-PPO-b-PBLG) triblock copolymers were synthesized by ring-opening polymerization of g-benzyl-L-glutamate-N-carboxyanhydride (BLG-NCA) initiated by NH 2 -PPO-NH 2 [46][47][48]. NH 2 -PPO-NH 2 (0.2 g; 0.05 mmol) and BLG-NCA (2.7 g; 10 mmol) was dissolved in dioxane separately in two flame-dried reaction bottles, then, BLG-NCA solution was added to the solution of NH 2 -PPO-NH 2 via a transfer cannula.…”
Section: Polymer Synthesis and Characterizationmentioning
confidence: 99%
“…Synthesis of Polypeptide Homopolymer PBLG homopolymer was prepared by a standard N-carboxyl-c-benzyl-Lglutamate anhydride (NCA) method [31,32]. The molecular weight of the PBLG homopolymer was estimated from the [g] value measured in dichloroacetic acid (DCA), according to the document [33].…”
Section: Structure and Performance Of Pva=pblg Blend Membranes 721mentioning
confidence: 99%
“…[17][18][19] The molecular weight of PBLG was estimated from the intrinsic viscosity measured in dichloroacetic acid (DCA). 24 The molecular weight of PBLG homopolymer used in the study is 50000.…”
Section: Syntheses Of Polypeptide Homopolymer and Copolymersmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Because of the unique structures and properties, synthesized polypeptides and their copolymers have been investigated widely in the fields of protein simulation, macromolecular conformational study, catalysis, drug delivery, nanoreactors etc. [13][14][15][16][17][18][19][20][21][22][23] Recently, much interest has been focused on the self-association behavior of the copolymers composed of hydrophobic polypeptide segments and hydrophilic polymer chains. 1,[7][8][9][10][11][12][13] Cho et al 9 have reported the formation of polymeric micelles composed of poly(γ-benzyl L-glutamate) and poly(ethylene oxide) in aqueous medium and the drug delivery system based on the core-shell nanoparticles with PBLG as the hydrophobic inner core and PEO as the hydrophilic outer shell.…”
Section: Introductionmentioning
confidence: 99%